2019
DOI: 10.1163/15709256-12341384
|View full text |Cite
|
Sign up to set email alerts
|

Liberalism and Conservatism in Relation to Psychological Type among Church of England Clergy

Abstract: Liberalism and conservatism have been important stances that have shaped doctrinal, moral and ecclesial beliefs and practices in Christianity. In the Church of England, Anglo-catholics are generally more liberal, and evangelicals more conservative, than those from broad-church congregations. This paper tests the idea that psychological preference may also partly explain liberalism or conservatism in the Church of England. Data from 1,389 clergy, collected as part of the 2013 Church Growth Research Programme, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
1
5
0
2
Order By: Relevance
“…-insert Table 3 about here -Other correlations are worth highlighting because they point to links between religious commitments and psychological factors. Conservative theological stances were generally associated with tendencies towards sensing, thinking and judging, associations that have be observed in other studies (see, for example, Village, 2019). Theological stance is related to church tradition in complex ways in the Church of England (Village, 2018b) and these trends were apparent in this sample.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…-insert Table 3 about here -Other correlations are worth highlighting because they point to links between religious commitments and psychological factors. Conservative theological stances were generally associated with tendencies towards sensing, thinking and judging, associations that have be observed in other studies (see, for example, Village, 2019). Theological stance is related to church tradition in complex ways in the Church of England (Village, 2018b) and these trends were apparent in this sample.…”
Section: Resultssupporting
confidence: 85%
“…The judging process is also associated with biblical literalism, but mainly because it tends to be a marker of general theological conservatism, with feeling types tending to be more liberal than thinking types (Village, 2019). This points to the thinking function's preference for tough-minded, logical decision-making that is based on logic and principles, even if that is upsetting to others, and the feeling function's preference for tender-minded decision-making that is based on values and that seeks for consensus, even at the risk of going against logic or principles.…”
Section: Psychological Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first has examined the correlations between religious dimensions and psychological type, with the aim of determining whether psychological type preferences are associated with particular expressions of faith or church life. These have shown that type the preferences of clergy and other ministers are related to many aspects of Christianity including charismatic experience (Francis & Jones, 1997), Christian conservativism (Village, 2016(Village, , 2019, tolerance for religious uncertainty (Francis & Jones, 1999), and different modes of faith expression (Francis & Louden, 2000;Francis, Craig, et al, 2008;Village, 2013).…”
Section: Psychological Type Studies Of Clergymentioning
confidence: 99%
“…Według Village'a konserwatyzm może się okazać ważniejszy dla interpretacji Biblii niż różnice między tradycjami religijnymi, do których wierzący przynależą (Village, 2016b(Village, , 2019. Konserwatyzm w kategoriach biblijnych skłania się ku dosłowności, zatem konserwatywni mogą wykazywać tendencje do przyjmowania bardziej konkretnych interpretacji i wykazywać nieufność wobec interpretacji spekulatywnych (Village, 2019). Częścią biblijnego konserwatyzmu jest biblijny literalizm (Village, 2016a).…”
Section: Biblijne Strategie Interpretacyjne: Konserwatyzm I Literalizmunclassified